IMPROVEMENT OF THE ENTERPRISE’S INNOVATIVE MANAGEMENT SYSTEM BASED ON STRATEGIC MANAGEMENT - Yuldasheva Kamola Miraliyevna (Ustozlar uchun, 2025)
The article discusses the methods of innovative development of construction material production enterprises, the prospects and stages of developing innovative strategies.